PENGARUH CORPORATE GOVERNANCE TERHADAP AUDIT DELAY PADA IDX 30 TAHUN 2019 - Debora Apriliyani Bakara; Harlyn Siagian (Jurnal Ekonomis, 2021)
This study was conducted to determine the effect of corporate governance on audit delay on the IDX in 2019. This type of research is quantitative using secondary data from the financial statements and annual reports of companies listed on the IDX in 2019. The research sample was obtained from 30 companies. listed on the IDX in 2019, with 30 research samples found. The variables of this study consist of independent variables, namely the Independent Board of Commissioners (X1) with data on the number of independent commissioners, and the Audit Committee (X2) with data on the number of audit committee members and the dependent variable Audit Delay (Y) with data on the number of days of delay in the publication of audit reports. This study uses descriptive statistical analysis, classical assumption test, and multiple linear regression. The results of this study prove that (1) the independent board of commissioners has a negative effect on audit delay (2) the audit committee has no significant effect on audit delay (3) the independent board of commissioners and audit committee have a significant influence simultaneously on audit delay.